The future of 5G smart home network security is micro-segmentation. Issue 11 (November 2020) - Wasicek, Armin
Abstract : IDC predicts that there will be around 41.6 billion connected IoT devices in 2025, and GSMA predicts 20% of connections will be 5G by the same year. 1 In a 5G world, many IoT devices will connect directly to the network, which will bring new cyber security challenges and opportunities alike. For carriers, providing strong cyber security built into their networks will be a competitive advantage at first, and ultimately will become a must-have for all carriers. IDC predicts that there will be around 41.6 billion connected IoT devices in 2025, and GSMA predicts 20% of connections will be 5G by the same year. In a 5G world, many IoT devices will connect directly to the network, which will bring new cyber security challenges and opportunities. For carriers, providing strong cyber security built into their networks will be a competitive advantage at first, and ultimately will become a must-have for all, according to Armin Wasicek of Avast.